Mental qualities of sprinters and stayers - Khokhlova, N. I.; Rodermel, T. A. (Theory and Practice of Physical Culture, 2019)
Objective of the study was to rate mental qualities of sprinters and stayers. Sampled for the study were 20-25 year-old athletes (n=13) including 7 sprinters and 6 stayers free of physical injuries/ health disorders, with the sample grouped as advised by the coaches. A comparative analysis of the mental qualities test data showed the high motivation and low mental control qualities and skills in the sample regardless of the distance; with the sprinters tested with the relatively higher aggression and anxiety rates than the stayers. The study data demonstrate the need for a special psychological support service to the athletes including the distance-specific mental conditioning tools. The authors offer a toolkit that may be helpful for the sport psychologists striving to analyze and improve the individual athletes` mental control qualities and skills for a competitive success; and list the priority fields for the psychological support service.